Common tumors in cats: A comprehensive review of epidemiological and clinicopathological aspects - Nadia Laissaoui; Daniela Simon Betz; Yolanda Millán; Meryem El Mrini; Rahma Azrib; Noursaid Tligui (Veterinary Integrative Sciences)
Feline tumors continue to be a rising problem in veterinary oncology. Knowledge of the actual epidemiological situation, circumstances of appearance and clinicopathological features of this pathology is essential to establish adequate diagnosis and preventive strategies, thus improving feline welfare. This review aims to update the current knowledge on three of the most common feline tumors: Squamous cell carcinoma (SCC), mammary tumors (MTs) and fibrosarcoma. For this, the recent epidemiological data published in scientific literature was summarized, potential risk factors incriminated in the occurrence of these tumors was explored, and their clinicopathological aspects were determined